Climate activism how communities take renewable energy actions across business and society - Skoglund, Annika 1977-; Böhm, Steffen 1973- (Cambridge University Press, 2022)
What is activism? The answer is, typically, that it is a form of opposition, often expressed on the streets. Skoglund and Böhm argue differently. They identify forms of 'insider activism' within corporations, state agencies and villages, showing how people seek to transform society by working within the system, rather than outright opposing it. Using extensive empirical data, Skoglund and Böhm analyse the transformation of climate activism in a rapidly changing political landscape, arguing that it is time to think beyond the tensions between activism and enterprise. They trace the everyday renewable energy actions of a growing 'epistemic community' of climate activists who are dispersed across organisational boundaries and domains. This book is testament to a new way of understanding activism as an organisational force that brings about the transition towards sustainability across business and society and is of interest to social science scholars of business, renewable energy and sustainable development
Keywords: Climatic changes / Prevention / Citizen participation; Climate change mitigation / Citizen participation; Electronic books